Impulse control disorders in Parkinson's: Sleep disorders and nondopaminergic associations. Issue 3 (10th February 2018) - Carbunaru, Samuel; Eisinger, Robert S.; Ramirez‐Zamora, Adolfo; Bassan, Dana; Cervantes‐Arriaga, Amin; Rodriguez‐Violante, Mayela; Martinez‐Ramirez, Daniel
Abstract: Objectives: Impulse control disorders (ICDs) are common among patients with Parkinson's disease (PD). Risk factors identified for developing ICDs include young age, family history, and impulsive personality traits. However, the association of these potentially disabling disorders with nondopaminergic drugs and sleep disorders has been understudied. Our objective was to examine the association between ICDs and nondopaminergic medications and sleep disorders. Methods: We conducted an observational study of 53 patients with PD from the National Institute of Neurology and Neurosurgery. ICDs were diagnosed using the Questionnaire for Impulsive–Compulsive Disorders in Parkinson's Disease Rating Scale (QUIP‐RS). Patients underwent polysomnography screening to diagnose the presence of sleep disorders. We documented the presence of dopaminergic and nondopaminergic medications, including monoamine oxidase type B inhibitors (MAOBIs), antidepressants, sleep inductors, and antipsychotics. Results: ICDs were reported in 18.9% of the patients ( n = 10), and sleep disorders were diagnosed in 81.1% of patients ( n = 43). 32.1% of the patients were on antidepressants, 17% on MAOBIs, 15.1% on sleep inductors, and 1.9% on antipsychotics. We observed that QUIP‐RS A–D subscore depended on the presence of antidepressants ( p = .03) and sleep inductors ( p = .02). Sleep disorders were not associated with the total QUIP‐RS score ( p = .93) or QUIP‐RS A–D subscore ( p = .81). Conclusion: Antidepressants and sleep inductors were significant predictors for individual QUIP‐RS items and subscores. Our results suggest that nondopaminergic drugs commonly used for PD may be associated with impulse control disorders. We did not identify a relationship between ICDs and polysomnography‐confirmed sleep disorders in patients with PD. Larger and longitudinal studies are needed to confirm our results. Abstract : This study examines the association between impulse control disorders (ICDs) and nondopaminergic medications and sleep disorders in patients with Parkinson's disease (PD). Our results suggest that nondopaminergic drugs commonly used for PD may be associated with ICDs. We did not identify a relationship between ICDs and polysomnography‐confirmed sleep disorders in patients with PD.